Factors affecting nurse efficacy self in implementing resusitation in cardiac arrest patients - Ahsan; Tualeka, Abdul Rohim; Rahmawati, Pudji; Russeng, Syamsiar S.; Susilowati, Indri H.; Jalaludin, Juliana (Universidad del Zulia, 2020)
Cardiac arrest is an emergency case illness that can be life-threatening if it does not get good treatment from a health worker. Research on self-efficacy against resuscitation cases in patients with heart disease are still small, especially in Indonesia. As a result, this paper tries to investigate the parameters that can be effective in self- efficacy. The factors that influence the most dominant self-efficacy are mastery experience. But it must also take into account other factors such as verbal exploitation, because environmental and management support is one of the important factors in increasing the ability to do resuscitation in patients with cardiac arrest.